Association of Typical Toxic Heavy Metals with Schizophrenia - Ma, Jiahui (Int J Environ Res Public Health, 2019)
Toxic heavy metals (THMs) are contaminants commonly found in the environment. Although a large number of studies have demonstrated their damage to the biological functions of the human being, their potential associations with the risk of developing schizophrenia remain controversial. In this study, we investigated the associations between four THMs (chromium (Cr), cadmium (Cd), lead (Pb) and arsenic (As)) in serum and the risk of schizophrenia. In total, 95 patients with schizophrenia (cases) and 95 normal subjects (controls) were recruited from Hebei Province, China. The serum concentrations of the 4 THMs were analyzed by inductively coupled plasma mass spectrometry (ICP-MS). A higher concentration of Pb was found significantly associated with an elevated risk of schizophrenia (OR = 3.146; 95%CI: 1.238–7.994, p = 0.016), while significant association for the other three THMs were not observed. Besides, significant correlations were found between the metabolic biomarkers and the concentrations of Pb and As, respectively. In order to further characterize the association between these THMs and schizophrenia with greater statistical power, we conducted meta-analysis by including 538 cases and 1040 controls from the current study and 5 available datasets published from 2002 to 2018. Using a random-effect model, Cr was significantly associated with schizophrenia (SMD = 0.3246; 95%CI: 0.0166–0.6326, p < 0.01). Overall, this study suggested that higher levels of Pb and Cr may be one of the factors associated with an elevated risk of schizophrenia.